Three-dimensional finite element analysis of a porcelain crowned tooth - Bankole.I. Oladapo (Beni-Suef University Journal of Basic and Applied Sciences, 2018)
The restoration of endodontically treated teeth is one of the main challenges in restorative dentistry since the weakened tooth structure is more prone to biomechanical failures due to significant tooth loss. The aim of this paper is to computational analysis of prepared crowned tooth in order to differentiate the possibility of using porcelain material for typical clinical condition and masticatory load by using the three-dimensional finite element method (3D FEM). In order to have an accurate geometry of tooth model, a coordinate measuring machine (CMM) is proposed to scan the tooth. The obtained scanned contours exported to ABAQUS FE package for computational stress analysis. The prosthodontics crown FEM has been created and put on simulated chewing stresses. The model is composed of four different materials, namely; prepared tooth, luting cement, substructure (IPS Empress Core), and Ingot (IPS Empress Layer). The generated FEM run and the stress distributions of the crowned tooth is thoroughly investigated. The developed model is extremely useful for indicating tooth biomechanics and has the tendency to deliver a better understanding to designers in the biomedical engineering field and dentistry. Keywords: Finite element method, Porcelain crowned tooth, Stress analysis, Dentistry